2020
DOI: 10.1177/1591019920947857
|View full text |Cite
|
Sign up to set email alerts
|

Impact and prevention of errors in endovascular treatment of unruptured intracranial aneurysms

Abstract: Background Preventing errors and complications in neurointervention is crucial, particularly in the treatment of unruptured intracranial aneurysms (UIAs), where the natural history is generally benign, and the margin of treatment benefit small. We aimed to investigate how neurointerventionalists perceive the importance and frequency of errors and the resulting complications in endovascular UIA treatment, and which steps could be taken to prevent them. Methods An international multidisciplinary survey was condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…These results are in line with our findings: all of our trainees rated the learning and practice effect of the initial simulator training at the end of the curriculum as very valuable. Simulation training has also been described to be one important factor in preventing technical and cognitive errors that may result in complications during neuroendovascular procedures [ 5 , 16 ]. In this context, our study participants rather disagreed that the simulator approach provides awareness of typical complications during endovascular procedures.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in line with our findings: all of our trainees rated the learning and practice effect of the initial simulator training at the end of the curriculum as very valuable. Simulation training has also been described to be one important factor in preventing technical and cognitive errors that may result in complications during neuroendovascular procedures [ 5 , 16 ]. In this context, our study participants rather disagreed that the simulator approach provides awareness of typical complications during endovascular procedures.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Ospel et al [51] conducted an international multidisciplinary survey, with the intention of determining the point of view of neurointerventionalists about the errors regularly committed in the endovascular treatment of unruptured intracranial aneurysms. They found that the faults that most regularly caused complications were related to technical execution and suggested that these faults can be prevented by strengthening the abilities of medical personnel through training in simulation settings.…”
Section: Simulation In Neurovascular Critical Carementioning
confidence: 99%
“…They found that the faults that most regularly caused complications were related to technical execution and suggested that these faults can be prevented by strengthening the abilities of medical personnel through training in simulation settings. As a result, it would be ideal for simulation to be widely available to physicians and to become a part of the equipment in intervention centers, similar to surgical specialties that use this learning modality permanently in their academic training program [51][52][53].…”
Section: Simulation In Neurovascular Critical Carementioning
confidence: 99%